2017
DOI: 10.1002/pip.2902
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of commercial triple junction concentrator solar cells under real climatic conditions and its influence on electricity cost

Abstract: This paper proposes a methodology for assessing the concentrator solar cell reliability in a real application for a given location provided the results from accelerated life tests. We have applied this methodology for the evaluation of warranty times of commercial triple junction solar cells operating inside real concentrator modules in Golden (Colorado, USA), Madrid (Spain) and Tucson (Arizona, USA) for the period 2012-2015. Warranty times in Golden and Madrid, namely, 68 and 31 years, respectively, for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…Following the finite element calculations by Marta Victoria et al 32 , a 70 °C operation temperature has been assumed as representative of small (1 mm 2 ) cells with excellent passive cooling (directly attached to a copper plate) under high concentrated irradiance (1000 suns) 32 . This is a best case scenario with current technology, but choosing such a low operation temperature might be justified as reliability studies have shown that good heat extraction can prolong the life of concentrator solar cells by decades 34 . A minimum temperature at zero irradiance of 15 °C is assumed.…”
Section: Methodsmentioning
confidence: 99%
“…Following the finite element calculations by Marta Victoria et al 32 , a 70 °C operation temperature has been assumed as representative of small (1 mm 2 ) cells with excellent passive cooling (directly attached to a copper plate) under high concentrated irradiance (1000 suns) 32 . This is a best case scenario with current technology, but choosing such a low operation temperature might be justified as reliability studies have shown that good heat extraction can prolong the life of concentrator solar cells by decades 34 . A minimum temperature at zero irradiance of 15 °C is assumed.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the photogeneration is corrected accordingly applying a wavelength‐dependent factor as suggested elsewhere 11,12 . Changes in the operating temperature (owing to a lower absorption as the substrate is thinned down) are not considered, as it will be highly dependent on the encapsulation and operating conditions of each device in particular 39,40 . Consequently, the temperature is set to 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…and the device packaging (solar cell size, thermal dissipation block, etc.) in a given solar panel 39,40 …”
Section: Modeling Of Thinned Ge Solar Cellsmentioning
confidence: 99%
“…14 It has been observed that locations with the higher irradiance are not always the most costeffective for PV applications due to reliability reasons. 29 In the literature, there is an interesting work that analyzes the degradation of PV power for the different climates of Köppen-Geiger climate 12 : A (tropical), B (dry), C (temperate), D (continental), and E (polar). In high-temperature climates, PV plants show more evident degradation mechanisms (1.13%/year).…”
Section: Influence Of Degradation In the Warranty Analysismentioning
confidence: 99%